2019
DOI: 10.14202/vetworld.2019.305-308
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of pigs raised by intensive management system in Abuja, Nigeria

Abstract: Background: Population growth led to an increase in the number of people raising pigs, resulting in increased demand for piglets/pigs for breeding and pork for consumption. Aim: This study was carried out to determine the reproductive performance of pigs raised by the intensive management system in Abuja, Nigeria, with a view to assist farmers in ensuring improved productivity and profitability. Materials and Methods: Using an interview-based questionnaire, data from 121 sows and 649 preweaning piglets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
1
2
Order By: Relevance
“…For sows, a total of 195 litters with a mean ± standard deviation of 7.2 ± 2.3 (with a range from 1 to 13) had been farrowed by 157 sows between July 2018 and March 2020. The TBA values are comparable to those reported in India and Nigeria ( Kumaresan et al, 2007 ; Abah et al, 2019 ) but lower than those reported in commercial herds in Uganda ( Okello, 2015 ). A total of 110 litters of 94 sows had weaning records on the total number of piglets weaned, the season of farrowing, parity, geographic location of the farm, and the pig housing system practiced on the farm.…”
Section: Resultssupporting
confidence: 70%
“…For sows, a total of 195 litters with a mean ± standard deviation of 7.2 ± 2.3 (with a range from 1 to 13) had been farrowed by 157 sows between July 2018 and March 2020. The TBA values are comparable to those reported in India and Nigeria ( Kumaresan et al, 2007 ; Abah et al, 2019 ) but lower than those reported in commercial herds in Uganda ( Okello, 2015 ). A total of 110 litters of 94 sows had weaning records on the total number of piglets weaned, the season of farrowing, parity, geographic location of the farm, and the pig housing system practiced on the farm.…”
Section: Resultssupporting
confidence: 70%
“…The difference was because, in the latter, the sows were native breeds that were extensively reared. The litter size was also higher than 7.2±1.1 reported among intensively reared in Nigeria (Abah et al, 2019).…”
Section: Results and Discussion Reproductive Performancecontrasting
confidence: 58%
“…The cumulative mortality rate of 18.4 % during the first 7 days of age was higher than 8.6% reported by Nuntapaitoon et al, 2018 in Thailand. On the contrary, the pre-weaning was lower than 31% reported in Nigeria (Abah et al, 2019).…”
Section: Piglet Mortalitycontrasting
confidence: 60%
“…Due to the high incidence, splay leg syndrome was the second most common cause of piglet mortality (22%) with a general lethality of up to 50% according to recent studies (5,28). The significance of this disease with regard to the economic losses and its negative effect on animal welfare and health is considerable and should not be underestimated (6,13,17).…”
Section: Incidence and Mortalitymentioning
confidence: 99%